Optimal Taxation, Global Externalities and Labor Mobility - Thomas Aronsson; Sören Blomquist (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper addresses transboundary environmental problems in the context of an optimal tax problem, when part of the labor force is mobile across countries. The policy instruments include both commodity taxation and nonlinear income taxation. We show how the tax policy in a noncooperative equilibrium differs from that corresponding to a cooperative equilibrium. The results also indicate how a 'global policy maker' must act in order to make the national policy makers replicate the cooperative equilibrium.
Keywords: 330; Transboundary externalities; fiscal federalism; optimal taxation